Hubungan antara Self-Management dengan Perilaku Agresi pada Siswa SMA - Amaliasari, Risqi Dwi; Zulfiana, Uun (Cognicia, 2019)
Aggression behavior among high school students or teenagers is still often found, for example: brawls, bullying. A person will behave aggressively so he will think first in acting so that he is able to manage himself (self management).The purpose of the study was to determine the relationship between self management and aggression behavior in high school students. This study uses a quantitative non-experimental approach. The subjects were 217 students of class X and XI SMA taken by stratified sampling technique. The research instrument uses the scale of aggression behavior and self management scale. The method of data analysis was the product moment correlation. Data analysis was carried out with the help of SPSS version 22.0. The results showed a value (r) of -0.122 with p was 0.037 <0.05. This shows that there is a significant negative relationship between self management and aggression behavior in high school students. The contribution of self management to aggression behavior is 1,5% (=0.015)